Optimum and clinical factors affecting the stable maintenance dose of warfarin at Ratchaburi Hospital - Mueanjanjaem, Kannika (Hua Hin Medical Journal, 2020)
Background : Warfarin is the most widely used oral anticoagulant in Thailand. Its indication is the prevention and treatment of thromboembolism. Warfarin has several limitations because of its narrow therapeutic index and the large inter-individual variability in dosing requirement making it a very problematic drug to prescribe. Several factors can affect the patients’ response to warfarin. Objective : To determine an optimum stable maintenance dose of warfarin in patients and impact factors; gender, age, body weight, comorbidity, and concurrent drugs on warfarin treatment at Ratchaburi hospital. Methods : The study design was a retrospective cohort study in outpatients who received warfarin during 1st October 2018 to 30th September 2019. All patients in the study were over the age of 18. Data were analyzed using descriptive statistics, Chi-square, and Pearson’s correlations to determine the association and relationship between the factors and the warfarin dose. Results : The results showed that in 328 patients, 165 use warfarin for atrial fibrillation (50.30%). An average warfarin daily dose for patients with a target international normalized ratio (INR) of 2.0-3.0 was 3.11±1.29 mg/day and with a target INR of 2.5-3.5 was 3.68±0.94 mg/day. The significant factors were age (r=-0.426, p=0.0001) and body weight (r=0.201, p=0.001). The older patients tended to receive<s>d</s> lower dose, the high body weight patients tended to receive<s>d</s> higher dose of warfarin. Conclusion : Age and body weight were found to be the significant factors that affected the warfarin requirement at Ratchaburi Hospital.